2017
DOI: 10.1177/2325967117729809
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Lever Sign Test in the Diagnosis of Anterior Cruciate Ligament Injuries

Abstract: Background:The lever sign test is a new physical examination tool to diagnose anterior cruciate ligament (ACL) tears. Preliminary results suggest almost 100% sensitivity and specificity to diagnose acute and chronic complete ACL tears and clinically significant partial tears as compared with magnetic resonance imaging (MRI).Purpose:To assess the sensitivity and specificity of the lever sign test for the diagnosis of acute ACL injuries, as compared to MRI. We also aimed to determine the accuracy of the lever si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
77
2
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(97 citation statements)
references
References 30 publications
2
77
2
6
Order By: Relevance
“…Massey et al [36] estimated the sensitivity of the test to be 83%, and the authors suggest that such a high diagnostic value reported in the original paper might have been caused by the methodology of the study in which the author verified his test on patients with known ACL deficiency, which could have affected the final result. Furthermore, in a study published by Jarbo et al [37], high sensitivity was again not confirmed. What is worth noting is the fact that this examination, contrary to others tested in the study, was independent of patient relaxation, and therefore it might be utilized in daily practice in an acute setting.…”
Section: Discussionmentioning
confidence: 86%
“…Massey et al [36] estimated the sensitivity of the test to be 83%, and the authors suggest that such a high diagnostic value reported in the original paper might have been caused by the methodology of the study in which the author verified his test on patients with known ACL deficiency, which could have affected the final result. Furthermore, in a study published by Jarbo et al [37], high sensitivity was again not confirmed. What is worth noting is the fact that this examination, contrary to others tested in the study, was independent of patient relaxation, and therefore it might be utilized in daily practice in an acute setting.…”
Section: Discussionmentioning
confidence: 86%
“…10,11 Individual modifications of the tests with varying degrees of tibial rotation and the magnitude of examiner experience have been reported to influence test accuracy. 12,13 The Lachman test is performed in the supine position with the knee in ∼20°of flexion. Whether the test results are interpreted as dichotomous (positive = torn and negative = intact) or graded (grades I, II, and II), there is a subjective element to the data.…”
mentioning
confidence: 99%
“…Whether the test results are interpreted as dichotomous (positive = torn and negative = intact) or graded (grades I, II, and II), there is a subjective element to the data. 13,14 The clinician relies on the subjective assessment of end feel and being able to determine millimeters of translation to assign a grade of I (<5 mm), II (5-10 mm), or III (>10 mm). 14 A study by Makhmalbaf et al 5 reported the sensitivity of the Lachman test to be 93.5% with a significant difference between men and women (66.7% vs 94.6%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22 Thus, much interest has focused on the value of utilizing the magnetic resonance imaging (MRI) to preoperatively measure and glean information on autograft size, given the strong recommendation for its use as part of the overall diagnostic evaluation of patients with suspected ACL injury. 13 In fact, with regard to detecting ACL injury, MRI boasts a 97% sensitivity, 100% specificity, 100% positive predictive value, 96% negative predictive value, and 98% accuracy, 23,24 and additionally, has been instrumental in identifying associated meniscal, articular cartilage, subchondral bone bruise, and collateral ligament pathology. 14,25 However, its value in preoperatively predicting commonly used autograft sizes remains unknown.…”
mentioning
confidence: 99%